In-hospital cardiac arrest epidemiology and intervention - Ali Ismaeil (Sirte Journal of Medical Sciences, 2024)
Introduction: Sudden cardiac arrest (SCA) is the abrupt loss of all cardiac activities as a result of acute heart rhythm disturbance and cessation of respiration, it is the most critical condition that faces any healthcare system, and that requires accurate precise coordinated intervention to achieve a favourable outcome. The epidemiological figures and the survival rates of in-hospital cardiac arrest vary significantly between developed and developing countries owing to the availability of rapid response resuscitation teams and advanced healthcare facilities. This study dictated to examine the epidemiology and the intervention aspects of in-hospital cardiac arrest in the city of Sirte at Ibn Sina Teaching Hospital. Methods: This study is a cross-sectional survey, dedicated to examining the epidemiological and intervention data of in-hospital cardiac arrest at IBN SENA TEACHING HOSPITAL in the city of Sirte, used a data collection form that included details of interest, a total of 591 files for patients who were admitted to the intensive care unit during the study period, 50 cases of cardiac arrest were registered and included in this study for analysis. Results: a total of 50 cases, with an overall incidence of 5.4 cardiac arrests for every 1000 admissions. males were arrested more than females during the study period; 66% males (34 cases) and 32% females (16 cases), the age group that has the highest frequency of cardiac arrest was (>75 years old) group for both sexes, and almost all of the registered cases were in the ICU, even though only 23 cases 46% were resuscitated, respiratory system diseases were the most frequent aetiology for cardiac arrest during the study period, followed by trauma and came 3rd the cardiovascular system diseases, Concomitant comorbidity of HTN and DM represents the most frequent pre-arrest illnesses which, and finally the survival rates were zero. Very important data were missed/undocumented that could improve the survival rates in one way or the other